Biological Synthesis of Gold Nanoparticles by Cell Free Supernatant of Streptomyces sp. ERI-3 - Faghri Zonooz, Neda; Salouti, Mojtaba (Asian Journal of Chemistry, 2012)
In present study, in vitro biosynthesis of gold nanoparticles (GNPs) was achieved using HAuCl4 as a substrate by Streptomyces sp. ERI-3 cell-free supernatant. The formation of gold nanoparticles was confirmed by UV-VIS sperctrophtometry, X-ray diffraction and scanning electron microscopy. Gold nanoparticles were formed after 48 h of incubation at 28 ºC and pH 7.